Telaah Teori, Metode dan Desain Arsitektur Bioklimatik Karya Ken Yeang - I Kadek Merta Wijaya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
Increased demand for residential housing along with the development of human population over time increasing in number, while the land to accommodate those needs tend to be fixed. The presence of skyscrapers buildings as a solution to the problems of land availability is shrinking. But the presence of skyscrapers buildings will require the need for energy in the building process - for example the circulation, the use of air conditioning or for lighting - are increasing as well. This is because the design of building skyscrapers tend to require large energy resources in the operation. While the availability of natural resources over time diminishing in the face of the earth in occupying the demand for energy. Unlike the traditional building which to focus on the concept of eco-friendly and not too much exploring natural resources in process. Ken Yeang's designs are different from other architects. Ken Yeang see the building skyscrapers today such as a refrigerator or freezer is cold and cool in it, but the heat outside. Ken Yeang trying to create a harmonious building with an Environmental in which the building is located. Purpose of this research to analyze the theories or concepts, methods and applications of architect Ken Yeang in response to the above phenomena. The method used in this study was content analysis.